KONSTRUKSI NILAI-NILAI NASIONALISME DALAM LIRIK LAGU (ANALISIS SEMIOTIKA FERDINAND DE SAUSSURE PADA LIRIK LAGU “MENOLEH” OLEH PANDJI PRAGIWAKSONO) - Aýun Masfufah (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2020)
This study aims to determine the construction of nationalism values in song lyrics. A song must have a message to be conveyed by the creator who then has a match between the meaning of the song lyrics and the reality. This study uses a semiotic analysis of Ferdinand De Saussure, the object of his research is a song lyric which is analyzed by each verse. In this analysis the steps taken are (1) determining the sign of the song lyrics that represent the object of research (2) writing a marker (signifier) or physical form, namely the lyrics of 'Menoleh' by Pandji Pragiwaksono (3) writing a sign that is the concept of markers (4) sees between signs, forms of signs, concepts of signs with social reality. This study explains the values of nationalism formed into a song lyrics and then uploaded into a song that is pitched and becomes a work that can be enjoyed. The work has the values of the struggle of the heroes and the young generation today must continue the struggle for the advancement of the Indonesian nation.